Preparation of biochar from food waste digestate: Pyrolysis behavior and product properties. (April 2020) - Liu, Jingxin; Huang, Simian; Chen, Kai; Wang, Teng; Mei, Meng; Li, Jinping
Highlights: Food wastes digestate was used to prepare biochars by pyrolysis. Eα was calculated by Starink method as 144.64–293.36 kJ/mol. The evolutions of volatiles were accurately and continuously analyzed by TG–FTIR–MS. Dehydration, CO2 and hydrocarbon emission were main reactions during the pyrolysis. Properties of biochars at different temperatures were systematically characterized. Abstract: Solid digestate generated in the anaerobic digestion of food wastes was evaluated as a potential feedstock for biochar preparation by pyrolysis in this study. To understand the pyrolysis mechanism, thermogravimetric experiments were firstly implemented at different heating rates, then apparent activation energy during pyrolysis was calculated by using the Starink isoconversional method, ranging from 144.64 kJ/mol to 293.36 kJ/mol with the conversion increasing in the region from 0.10 to 0.90. The evolutions of released volatiles were accurately and continuously analyzed by TG–FTIR–MS. Results show that dehydration and CO2 emission were the main reasons for mass loss, and light hydrocarbons were released in step II of the pyrolysis process. Elemental compositions and surface properties of the biochars obtained at different pyrolysis temperatures were characterized by EA, XRF and BET. The obtained results provide an alternative strategy for disposing waste generated in anaerobic digestion of food waste.